Sciencepreneurship-Based Community Empowerment Model for Developing Appropriate Technology to Improve Rural Communities’ Entrepreneurial Intention - Zulpan, Zulpan; Prayogi, Saiful; Kurnia, Nova (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
This study aimed to evaluate the effectiveness of a sciencepreneurship-based community empowerment model in developing appropriate technology to improve the entrepreneurial intention (EI) of rural communities. The study was conducted in Krayan Jaya Village, Long Ikis District, Paser Regency, East Kalimantan, involving 40 participants divided into two groups: an appropriate technology group for producing tote bags made from spunbond fabric (Group A) and an appropriate technology group for developing a solar-powered water pump (Group B). This study employed a mixed-methods approach with an explanatory sequential design. The quantitative phase used a quasi-experimental multi-group pretest-posttest design, while the qualitative phase involved observation and semi-structured interviews. Entrepreneurial intention was measured using a 20-item Likert-scale questionnaire covering entrepreneurial orientation, internal motivation, risk-taking courage, and self-perception as a prospective entrepreneur. The data were analysed using descriptive statistics, assumption testing, the Wilcoxon signed-rank test, N-gain, ANCOVA, and thematic analysis. The results showed that the mean EI score of Group A increased from 50.80 to 78.45, with an N-gain of 0.56, while that of Group B increased from 52.00 to 74.50, with an N-gain of 0.48. The Wilcoxon test indicated significant improvement in both groups (p < 0.001). ANCOVA showed a significant difference in effectiveness between the groups after controlling for pretest scores (F = 7.156; p = 0.011; partial eta squared = 0.162), with the adjusted mean of Group A higher than that of Group B. The qualitative data revealed that involvement in appropriate technology development, institutional support, and business opportunities strengthened EI, whereas limited capital, fear of failure, technical complexity, and marketing challenges acted as barriers. This model is relevant for participatory, contextual, and sustainable rural community empowerment, particularly when supported more systematically by village-owned enterprises and local facilitators.